An ABC transporter controls export of a Drosophila germ cell attractant. - Ricardo, S.; Lehmann, R. (Science, 2009)
Directed cell migration, which is critical for embryonic development, leukocyte trafficking, and cell metastasis, depends on chemoattraction. 3-hydroxy-3-methylglutaryl coenzyme A reductase regulates the production of an attractant for Drosophila germ cells that may itself be geranylated. Chemoattractants are commonly secreted through a classical, signal peptide-dependent pathway, but a geranyl-modified attractant would require an alternative pathway. In budding yeast, pheromones produced by a-cells are farnesylated and secreted in a signal peptide-independent manner, requiring the adenosine triphosphate-binding cassette (ABC) transporter Ste6p. Here we show that Drosophila germ cell migration uses a similar pathway, demonstrating that invertebrate germ cells, like yeast cells, are attracted to lipid-modified peptides. Components of this unconventional export pathway are highly conserved, suggesting that this pathway may control the production of similarly modified chemoattractants in organisms ranging from yeast to humans.